A filosofia prática de Grice: análise do discurso prático e sistema de fins - Giarolo, Kariel Antonio (2016)
This doctoral dissertation has as main goal to reconstruct and to analyse central aspects of Grice s practical philosophy, in special, his conception of eudaimonia. My central proposal is to show that there is an inconsistency in the system of ends proposed by Grice in order to treat the philosophical problem of the nature of eudaimonia. In Aspects of Reason, Grice will determine what the nature of reason consists in and the philosophical consequences that follow from its adequate determination. Grice will discuss the relations between theoretical and practical reasoning, in order to maintain that theoretical and practical reason are developments of a single fundamental conception of reason. One of Grice s main thesis, after discussing the structure of rationality and presenting the so called theoretical and practical acceptabilities which are treated as special kinds of arguments that contains a basic rationality operator , is to defend that eudaimonia should be understood as an inclusive end. Furthermore, Grice presents a system of ends with formal features that will help the individuals in the search for their own eudaimonia. This system of ends would have as a function the organization of the constitutive ends of eudaimonia, in such a way that eudaimonia could be considered as a set of ends. In this view, the system of ends should ensure, among other things, the stability and consistence of the set of eudaimonia. However, by maintaining that eudaimonia is an inclusive end, and consequently a set of ends, Grice is inevitably led to an inconsistency, ignored by him. The treatment of eudaimonia as an end and simultaneously as a set of ends implies a formal problem. According to one of the axioms of the set theory, the Axiom of Regularity, a set cannot be a member of itself. So, I intend to defend that Grice s systems of ends, but to criticize his thesis that eudaimonia can be considered as a set of ends. My alternative proposal is that the best option is to treat eudaimonia through mereology, i.e., the theory of the whole and their parts.